Mentawai Forest and Tradition: Maintaining the Balance of Nature and Culture - Sabagalet, Yudas; Zulfa, Zulfa (Bhandar: Harvesting Community Service in Asia, 2024)
Tropical forests in the Mentawai Islands have a very important role in the lives of the Mentawai people, both as natural resources and as a center of culture and spirituality. The purpose of this study is to examine the relationship between forests and the traditions of the Mentawai people, and how the sustainability of nature and culture are maintained in their daily lives. This research method is qualitative with an approach to oral tradition, ethnography, sociological anthropology. Data collection techniques are observation, interviews, documentation studies. Data analysis techniques using reduction, data presentation and data verification or drawing conclusions. The results of this study are: The Mentawai people utilize forest resources in a very wise way, based on local wisdom that has been passed down from generation to generation. However, the Mentawai forest is currently facing various threats, such as deforestation and land conversion, which have an impact on the sustainability of their culture. By exploring the importance of Mentawai traditions in forest management and the challenges faced.